Severe pulmonary-renal syndrome in honeybee sting envenomation – A case report - Alan Shaji; Malik Parvez; Naresh Kumar Chirumamilla; Nalin Sharma; Ashok Kumar Pannu (Turkish Journal of Emergency Medicine)
Honeybee stings with features of envenomation (either local or allergic and rarely systemic toxicity) are often seen in agriculture workers. An initial presentation with severe diffuse alveolar hemorrhage or pulmonary-renal syndrome is rare and only confined to a few case reports. Herein, we describe a case of a 45-year-old male who presented with multiple bee stings and subsequently developed acute kidney injury and pulmonary hemorrhage. He was managed with hemodialysis, invasive mechanical ventilation, red-cell transfusion, and pulse methylprednisolone. However, he developed cardiac arrhythmias with ventricular tachycardia and died.